Розробка окулярів для людей з обмеженими можливостями - Білошапка, І. В. (ХНУРЕ, 2022)
This article discusses the concept of glasses for people with disabilities. The main components of technology, its main purpose and tasks are considered. Key features, advantages and disadvantages of the concept . Conclusions are drawn about the relevance of technology today, its progress and development . All options and technologies used in this project . And how can obsolete technology be improved . That one can look at the characteristics of the finished product.
Keywords: мобільні додатки; ультразвукові окуляри; люди з обмеженими можливостями